Pengaruh Perceived Crowding terhadap Memorable Experience dan Behavioral Intention dengan Variabel Moderasi Fandom dalam Konser Blackpink Jakarta 2023 - Ayuningtyas, Shafira Rahma; Sujatno, Teresa Cindy; Soehadi, Agus W.; Jayawardhana, Irman (Stupa, 2024)
Blackpink, a South Korean music group, held a concert at the Gelora Bung Karno Main Stadium on March 11-12, 2023, bringing in a total of 140,000 audiences. This phenomenon became the talk of the town because it had a big impact. The crowd created a memorable experience and increased the desire to watch the BLACKPINK concert again in Jakarta. Aims to analyze the effect of Perceived Crowding on Memorable Experience (MME) and Behavioral Intention with moderating variable Fandom using a quantitative approach. This study collected 403 respondents and the data was processed mean test, standard deviation test, discriminant validity test, EFA test, CFA test, and MGA test using SPSS and AMOS. The result is that there is a significant influence between the four variables and the role of the moderating variable of high Fandom level can strengthen and improve the relationship with MME. Next, the research can be further developed by choosing a more specific geographical location and examining a different context. Through this research we hope to help readers, academics, and event actors to pay attention to the crowd in an event.